Climate change in human history : prehistory to the present - Lieberman, Benjamin, 1962-; Gordon, Elizabeth (Professor) (London ; New York : Bloomsbury Academic, 2022)
"Climate Change and Human History provides a concise introduction to the relationship between human beings and climate change throughout history. Starting hundreds of thousands of years ago and going up to the present day, this book illustrates how natural climate variability affected early human societies and how human activity is now leading to drastic changes to our climate. Taking a chronological approach the authors explain how climate change created opportunities and challenges for human societies in each major time period, covering themes such as phases of climate and history, climate shocks, the rise and fall of civilizations, industrialization, accelerating climate change and our future outlook. This 2nd edition includes a new chapter on the explosion of social movements, protest groups and key individuals since 2017 and the implications this has had on the history of climate change, an improved introduction to the Anthropocene and extra content on the basic dynamics of the climate system alongside updated historiography. With more case studies, images and individuals throughout the text, the second edition also includes a glossary of terms and further reading to aid students in understanding this interdisciplinary subject. An ideal companion for all students of environmental history, Climate Change and Human History clearly demonstrates the critical role of climate in shaping human history and of the experience of humans in both adapting to and shaping climate change"--
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (Site, viewed 11/09/2023).
Keywords: Climatic changes -- Social aspects -- History; Human beings -- Effect of climate on -- History; Climate and civilization; Prehistoric peoples -- Climatic factors; Human ecology -- History